Bentonite intercalated organometallic complex as adsorbent of procion red - Lora Vitanesa; Radja Nardo Purba; Aldes Lesbani; Muhammad Said (Science and Technology Indonesia, 2017)
Insertion of bentonite with organometallic compounds [Cr3O(OOCH)6(H2O)3 (NO3)]as adsorbent of procion red with comparison weight ratio of bentonite: organometallic compounds [Cr3O(OOCH)6(H2O)3 (NO3)] i.e.: (2.5:1), (1:1), (1:2) and (1:3) has been done. The results of insertion bentonite were characterized using FT-IR spectrophotometer, XRD, and XRF. Furthermore, the product of optimum insertion was used as an adsorbent of procion red. The spectrogram from FT-IR shows the process of insertion was not optimum for every weight ratio. Characterization using XRD showed the optimum insertion process ratio (1:2) and (1:3) was indicated the presence of diffraction appearing at 2θ region by a shift in the diffraction angles 5.00 and 39o from the original activated bentonite of 20.8o. Characterization using XRF analysis in the ratio (1:3) shows percentage of metal oxide Cr2O3 increase to 82.28%, so at the ratio of 1:3, the process insertion of organometallic compounds into the bentonite has stated success base on its highest percentage. The adsorption process of insertion bentonite organometallic compounds [Cr3O(OOCH)6(H2O)3 (NO3)] ratio (1: 3) shows the magnitude of the rate of adsorption (k) at 0.004 min-1, the adsorption capacity (b), the largest at a temperature of 70oC at 72.99 mol/g, the largest adsorption energy (ΔG) at a temperature of 60oC i.e. 17.05 kJ / mol, the largest enthalpy (ΔH) is 105720.8 kJ/mol, entropy (ΔS) 315 kJ/mol and pH 11 has the biggest value of procion red adsorped, i.e. 33.38 mg/L. Keywords: Bentonite, Organometallic compound [Cr3O(OOCH)6(H2O)3(NO3)].Adsorption, Procion Red